Victor Frankenstein [videorecording (DVD)] - Radcliffe, Daniel, 1989-; McAvoy, James, 1979-; Findlay, Jessica Brown, 1989-; Scott, Andrew, 1976 October 21- (Twentieth Century Fox Home Entertainment, 2016)
Told from Igor's perspective, we see the troubled young assistant's dark origins, his redemptive friendship with the young medical student Viktor Von Frankenstein, and become eyewitnesses to the emergence of how Frankenstein became the man, and the legend, we know today.